Water vapor absorption between 5690 and 8340 cm−1: Accurate empirical line centers and validation tests of calculated line intensities. (April 2020) - Mikhailenko, S.N.; Kassi, S.; Mondelain, D.; Campargue, A.
Highlights: A line list is constructed for natural water between 5690 and 8340 cm −1 . We use the variational list by Schwenke and Partridge at starting point. Line centers are accurately determined from empirical values of the energy levels. The set of empirical energy levels gathers the best experimental information at disposal. The available theoretical line lists include transitions with intensities deviating importantly from the observations. Abstract: An accurate empirical list of 57, 995 transitions is constructed for natural water in the 5690–8340 cm −1 near infrared region (1.76–1.20 µm). The new list represents an updated version of the list reported in Mikhailenko et al. (2016). The spectral range is extended to lower energy and the transition frequencies benefited from a series of recent measurements by comb-assisted cavity ring down spectroscopy (CA-CRDS). The line list construction uses as starting point the variational line lists computed on the basis of the results of Schwenke and Partridge for the six most abundant water isotopologues (H2 16 O, H2 18 O, H2 17 O, HD 16 O, HD 18 O, HD 17 O). Variational line positions are replaced by position values calculated from empirical rotation-vibration energy levels. The set of required empirical energy levels is improved in accuracy and enlarged, in particular for the minor isotopologues. A large number of energy levels and thus transition frequencies, relying on spectra recorded by CA-CRDS, have accuracy on the order of 10 −4 cm −1 . All the transitions are provided with unique vibrational labeling supported by effective Hamiltonian calculations in case of ambiguity. A detailed comparison is presented with the list of natural water included in the HITRAN2016 database and with the very recent H2 16 O and H2 18 O lists reported in Conway et al. (2020). The advantage of our list in terms of line position accuracy is demonstrated and illustrated by direct comparison with CRDS recordings at disposal. Intensity comparison shows a general agreement but a number of weaknesses of the most recent intensity calculations are evidenced. All the considered theoretical line lists include a few bands ( e.g. 4ν2,  5ν2, ν1 +2ν2 and ν1 +3ν2 ) with intensities deviating significantly from the observations. Graphical abstract: Image, graphical abstract